Pressurized intraperitoneal aerosol chemotherapy procedure for nonresectable peritoneal carcinomatosis: First Indian study - Somashekhar, S. P. (South Asian J Cancer, 2019)
BACKGROUND: Peritoneal carcinomatosis (PC) is a common evolution of abdominal cancers and is associated with poor prognosis. A few selected patients have option of cytoreductive surgery and hyperthermic intraperitoneal chemotherapy, but majority who are not eligible for curative approach can undergo pressurized intraperitoneal aerosol chemotherapy (PIPAC). It is an emerging field of research with major therapeutic potential. It is a safe and innovative approach, which enhances the effect of chemotherapy without major toxicity. METHODS: Between June 2017 and December 2017, 21 PIPAC applications in seven patients with standard chemotherapy regimen every 6 weeks at 37°C and 12 mmHg for 30 min was performed. The patients’ demographics, perioperative findings, adverse events, and outcomes were prospectively recorded. RESULTS: Twenty-one PIPAC administrations were performed in 7 patients with PC from various pathologies. The median hospital stay was 1 day. All the patients had symptomatic relief with complete resolution of ascites. There was no major perioperative complications. CTCAE Grades 1 and 2 were observed in three patients, for abdominal pain and nausea. Renal and hepatic functions were not impaired. Of the seven patients, one patient had complete histological remission; three patients had partial response, one had stable disease and one patient had no response with clinical progression. CONCLUSION: Our results show the feasibility and safety of PIPAC in Indian patients. The procedure has low morbidity with no mortality with the short learning curve. It can be easily adapted for Indian patients with diffuse PC as a palliative option apart from systemic chemotherapy.